Pacta in favorem tertii sau tratatele prevăzând drepturi și obligații pentru statele terțe [Articol] - Osmochescu, Nicolae; Șiman, Augustina (CEP USM, 2018)
În prezentul demers ştiinţific urmărim scopul de a cerceta problematica drepturilor şi obligaţiilor generate de tratate faţă de state care nu sunt parte la acestea, precum şi importanţa exprimării consimţământului de către state terţe sau de către organizaţii internaţionale interguvernamentale terţe. Astfel, a fost analizat atât textul Convenției de la Viena cu privire la dreptul tratatelor din 1969, cât şi al Convenției de la Viena privind dreptul tratatelor dintre State și Organizații Internaționale sau dintre Organizații Internaționale din 1986 (neintrată în vigoare), fiind aduse în lumină tipuri relevante de tratate internaţionale, precum şi analizată practica Curţii Internaţionale de Justiţie. Totodată, combatem unele opinii doctrinare vis-à-vis de relevanţa speţei The Free Zones of Upper Savoy and the District of Gex Case (Curtea Permanentă de Justiţie Internaţională, 1932) în cazul pacta in favorem tertii.

The present scientific research aims to create a complex reflection study on the issue of rights and obligations generated by treaties for non-member states as well as on the importance of expressing consent by third states or by third party intergovernmental organizations. Thus, the text of both the Vienna Convention on the Law of Treaties of 1969 and the Vienna Convention on the Law of Treaties between States and International Organizations or International Organizations of 1986 (not yet in force) had been analyzed, highlighted relevant types of international treaties and examined the practice of the International Court of Justice. At the same time, this paper counterarguments some theoretical opinions regarding the relevance of the case of the Free Zone of Upper Savoy and the District of Gex (Permanent Court of International Justice, 1932) in the case of pacta in favorem tertii.
PACTA IN FAVOREM TERTII OR TREATIES WHICH CREATE RIGHTS AND OBLIGATIONS FOR A THIRD STATE
Keywords: Convenția de la Viena; tratat internațional; stat terţ; ONU; principiul egalităţii suvernane a statelor; Curtea Internaţională de Justiţie; Vienna Convention; pacta in favorem tertii; International Court of Justice; third international organization; UN